Sociologie du travail et sociologie économique en France (1945-1968) - François Vatin (La Nouvelle Revue du Travail)
This article discusses the theory formulated by promoters of the “new economic sociology,” according to which economic sociology experienced an “eclipse” in Europe as a whole, and in particular in France after the Second World War. According to this theory, in that time and place the dynamism of the “sociology of work” neglected the economic question. A close study of the content of the Treatise on the Sociology of Work directed by Georges Friedmann and Pierre Naville (1961-1962) and the journal Sociologie du travail from 1959 to 1968 shows that this theory is unfounded.